Effects of 8 weeks of 2S-Hesperidin supplementation on performance in amateur cyclists - Martínez-Noguera, F. J.; Marín-Pagán, C.; Carlos-Vivas, J.; Alcaraz, P. E. (Nutrients, 2020)
2S-Hesperidin is a flavanone (flavonoid) found in high concentrations in citrus fruits. It has an antioxidant and anti-inflammatory effects, improving performance in animals. This study investigated the effects of chronic intake of an orange extract (2S-hesperidin) or placebo on non-oxidative/glycolytic and oxidative metabolism markers and performance markers in amateur cyclists. A double-blind, randomized, placebo-controlled trial was carried out between late September and December 2018. Forty amateur cyclists were randomized into two groups: one taking 500 mg/day 2S-hesperidin and the other taking 500 mg/day placebo (microcellulose) for eight weeks. All participants completed the study. An incremental test was used to evaluate performance, and a step test was used to measure oxygen consumption, carbon dioxide, efficiency and oxidation of carbohydrates and fat by indirect calorimetry. The anaerobic power (non-oxidative) was determined using Wingate tests (30 s). After eight weeks supplementation, there was an increase in the incremental test in estimated functional threshold power (FTP) (3.2%; p = 0.05) and maximum power (2.7%; p = 0.05) with 2S-hesperdin compared to placebo. In the step test, there was a decrease in VO2 (L/min) (-8.3%; p = 0.01) and VO2R (mL/kg/min) (-8.9%; p = 0.01) at VT2 in placebo. However, there were no differences between groups. In the Wingate test, there was a significant increase (p = 0.05) in peak and relative power in both groups, but without differences between groups. Supplementation with an orange extract (2S-hesperdin) 500 mg/day improves estimated FTP and maximum power performance in amateur cyclists.